The incidence and predictors of in-stent stenosis after pipeline flow-diverter stenting for intracranial aneurysm treatment - You, Wei; Lv, Jian; Li, Zifan; Chen, Xiheng; Deng, Dingwei; Tang, Yudi; Li, Youxiang; Sun, Yong; Jiang, Yuhua (Frontiers in Neurology, 2023)
Background and Purpose Data of in-stent stenosis (ISS) after flow diverter (FD) implantation are scarce and confusing. In the present study, we sought to assess the incidence of ISS and identify predictors of ISS severity through ordinal logistic regression. Methods A retrospective review of our center's electronic database was conducted to identify all patients with intracranial aneurysms (IAs) who received Pipeline embolization device (PED) implantation between 2016 and 2020. Patient’s demographics, aneurysm characteristics, procedural information, clinical and angiographic outcomes were reviewed. ISS was quantitatively assessed on angiographic follow-ups and graded as mild (<25%), moderate (25–50%), or severe (>50%). Ordinal logistic regression was conducted to determine predictors of stenosis severity. Results A total of 240 patients with 252 aneurysms treated in 252 procedures were enrolled in this study. ISS was detected in 135 (53.6%) lesions with a mean follow-up time of 6.53 ± 3.26 months. The ISS was mild in 66 (48.9%) cases, moderate in 52 (38.5%) cases, and severe in 17 (12.6%) cases. All patients were asymptomatic, except for two with severe stenosis who presented with symptoms of acute cerebral thrombosis. Ordinal logistic regression identified younger age and longer procedure duration as independent predictors of a higher degree of ISS. Conclusion ISS is a common angiographic finding after PED implantation for IAs and is presented as a largely benign course through long-term follow-up. Patients with a younger age and longer procedure duration were at risk of developing a higher degree of ISS.